Influence of the quality of sleep on the masticatory muscle activity - a pilot study - Zieliński, Grzegorz; Byś, Aleksandra; Baszczowski, Michał; Ginszt, Michał; Suwała, Marta; Szkutnik, Jacek; Majcher, Piotr (Journal of Education, Health and Sport, 2018)
Introduction: Modern literature indicates an uptrend in the occurrence of sleep disorders. Currently, about 30-40% of adults are suffering from sleep disorders, which makes them one of the most common health problems of the population. The aim of the study: The determination of the quality of sleep on the muscle tension of the masticatory apparatus. Methods and materials: 27 adults volunteered to take part in the study. After the application of the exclusion criteria, 12 women (with an average age of 23 ± 1 year) have qualified. They were subsequently divided into two equal groups, in accordance with the guidelines of the Pittsburgh questionnaire: six women with a below 6 point result - high quality of sleep and six women with an over 6 point result (or higher) - low quality of sleep. Electromyographic activity of the anterior temporalis (TA) and masseter muscle (MM) was evaluated in resting mandibular position. Based on the electromyographic results, the values of the asymmetry indexes of the muscles of the masticatory apparatus muscles were calculated. The U Mann-Whitney test has been used for the statistical analysis, with the significance level of 0,05. Results: There were no significant differences in resting activity of the anterior temporalis, masseter muscles and the asymmetry index of the anterior temporalis between groups (p>0,05). There was the significant difference in the asymmetry index of masseter muscles between groups (p<0,05). Conclusions: The quality of sleep has no significant influence on the resting activity of masticatory muscles. The influence of the quality of sleep on the asymmetry index should be the object of further research. In order to verify this conclusion, the research should be carried out on a larger group of people.